Hexose-transport-deficient mutants of Chlorella vulgaris : Lack of transport activity correlates with absence of inducible proteins. - Sauer, Norbert (Planta, 1986)
Autotrophically grown cells of Chlorella vulgaris show a strong increase in the uptake rates for hexoses and for seven amino acids when incubated in the presence of hexoses. This increase is due to de-novo synthesis of three transport proteins: one forhexoses and two for amino acids. Mutants deficient in hexose transport were obtained after treatment of wild-type cells with acridine orange, followed by a selection procedure using the toxic hexose analogue, 2-deoxy-D-glucose. Moreover, the two amino-acid-transport systems could not be induced in these mutants by hexoses. The capacity to phosphorylate hexoses was identical in mutants and in the wild-type strain. The loss of transport activities can be correlated with the loss of certain radiolabeled protein bands on fluorograms of sodium dodecylsulfate-polyacrylamide gels. These proteins are assumed to be responsible for the different transport systems in the wild-type strain. With the help of additional mutants defective in one or two of the different aminoacid-transport systems, it has been attempted to assign the different transport activities to individual protein bands on the gel.